Sarcomatoid differentiation in renal cell carcinoma: prognostic implications - Dall'Oglio,Marcos F. (2005)
INTRODUCTION: Renal cell carcinoma with sarcomatoid differentiation is a tumor with aggressive behavior that is poorly responsive to immunotherapy. The objective of this study is to report our experience in the treatment of 15 patients with this tumor. MATERIALS AND METHODS: We retrospectively analyzed 15 consecutive cases of renal cell carcinoma with sarcomatoid differentiation diagnosed between 1991 and 2003. The clinical presentation and the pathological stage were assessed, as were the tumor's pathological features, use of adjuvant immunotherapy and survival. The study's primary end-point was to assess survival of these individuals. RESULTS: The sample included 8 women and 7 men with mean age of 63 years (44 - 80); follow-up ranged from 1 to 100 months (mean 34). Upon presentation, 87% were symptomatic and 4 individuals had metastatic disease. Mean tumor size was 9.5 cm (4 - 24) with the following pathological stages: 7% pT1, 7% pT2, 33% pT3, and 53% pT4. The pathological features showed high-grade tumors with tumoral necrosis in 87% of the lesions and 80% of intratumoral microvascular invasion. Disease-free and cancer-specific survival rates were 40 and 46% respectively, with 2 cases responding to adjuvant immunotherapy. CONCLUSIONS: Patients with sarcomatoid tumors of the kidney have a low life expectancy, and sometimes surgical resection associated with immunotherapy can lead to a long-lasting therapeutic response.